Summary report : the socioeconomic and biodiversity impacts of driven grouse moors and the employment rights of gamekeepers /: the socioeconomic and biodiversity impacts of driven grouse moors and the employment rights of gamekeepers. (2020) - Thomson, Steven; McMorran, R; Newey, Scott; Matthews, Keith; Fielding, Debbie; Miller, Dave; Glass, Jayne; Gandossi, Gianna; McMillan, Jenny; Spencer, Mike
No abstract available